Espaçamento de plantio e porta-enxertos para tangerina IAC 2019Maria - Pinho, Rafael Justel do (Universidade Federal de São Carlos, 2022)
In the search for an expansion framework for citrus farming in relation to table varieties, citrus breeding programs have been developing new varieties of tangerines. Among them is the IAC 2019Maria mandarin, developed by Centro de Citricultura Sylvio Moreira/IAC, which is an F1 hybrid from a controlled cross between Murcott tangor [Citrus reticulata x C. sinensis (L.) Osbeck] (female parent) and Pera sweet orange [C. sinensis (L.) Osbeck] (male parent). With this, the objective was to analyze the initial development of IAC 2019Maria mandarin grafted on different rootstocks and planting spacings. The experiments were carried out at the Agricultural Sciences Center of the Federal University of São Carlos, in Araras/SP. IAC 2019Maria mandarin plants were grafted on Rangpur lime (C. limonia Osbeck), Swingle citrumelo [C. paradisi Macfad. cv. Duncan x Poncirus trifoliata (L.) Raf.] and in TSxPT 14 and TSxPT 70 citrandarins [C. sunki (Hayata) hort. ex Tanaka x P. trifoliata cv. Rubidoux (L.) Raf.] with the planting of the orchard carried out in February 2018 in the following spacings: 2.0 x 6.0; 2.5 x 6.0 and 3.0 x 6.0 m. After three years of implantation of the orchard, no interference of the different spacings was observed in the initial vegetative development of the tangerine plants IAC 2019Maria. Regarding the rootstocks, significant differences were observed for the variables height, diameter, canopy volume and drought resistance. For plant height, diameter and canopy volume, it was observed that the TSxPT 14 citrandarin rootstock presented the lowest values, 1.41 m, 1.18 m and 1.07 m3, respectively, differing from the other rootstocks. grafts evaluated and being considered of low vigor with dwarfing power. The TSxPT 14 citrandarin was the most susceptible to drought and IAC 2019Maria mandarin showed initial symptoms of incompatibility with TSxPT 14 citrandarin.
Planting spacing and rootstocks for IAC 2019Maria mandarin
Keywords: Tangor; Tangerina IAC 2019Maria; Citrus; Adensamento de plantio; IAC 2019Maria mandarin; Planting density; CIENCIAS AGRARIAS::AGRONOMIA::FITOTECNIA